Preliminary results of revision of mineral-raw material base of opal-cristobalite rocks in middle Trans-Urals - Pavel Vitalievich Smirnov (Известия Томского политехнического университета: Инжиниринг георесурсов, 2017)
Relevance of the discussed issue. Opal-cristobalite rocks in terms of their spatial distribution and their resource potential are one of the main types of nonmetallic minerals in the Trans-Urals and potentially industry-forming for region. Due to the absence of revision geological exploration work, the available estimates of the resource potential, being the only ones presented in the literature, are obviously very approximate, are irrelevant and require additions. Revision works, on the one hand, are aimed at increasing the reserves of opal-cristobalite rocks, on the other hand they aim is to differentiate the productive strata by age, lithology and raw material quality in such a vast territory. When clarifying the geographic structure, systematizing objects and assessing the raw potential of the Trans-Urals subprovince, not only deposits but also areas of near-surface deposition of siliceous deposits potentially promising for opal-cristobalite raw materials should be taken into account. The main aim is the revision of the mineral base of opal-cristobalite rocks, identification of promising areas of prospecting works for all types of opal-cristobalite rocks in the Middle Trans-Urals. The methods used in the research: field research, reconnaissance studies, sampling. The results. Based on the study of stock geological literature, recommendations for thematic and geological survey, and field research on the study of natural and artificial outcrops of opal-cristobalite rocks, the author has identified the promising areas. The information on 12 promising sites on siliceous raw materials is updated, the information on four of them was introduced for the first time. The mineral-raw material base of opal-cristobalite rocks has huge prospects for increasing reserves, and the objects are located in areas with the developed transport and industrial infrastructure, which simplifies their industrial development and reduces the volume of capital expenditures.